Transcriptome Sequencing Identifies PLAUR as an Important Player in Patients With Dermatomyositis-Associated Interstitial Lung Disease - Chen, Juan; Zhang, Ruixian; Xie, Min; Luan, Chunyan; Li, Xiaolan (Frontiers in Genetics, 2021)
Dermatomyositis (DM), an inflammatory disorder, is often associated with interstitial lung disease (ILD). However, the underlying mechanism remains unclear. Our study performed RNA sequencing (RNA-seq) and integrative bioinformatics analysis of differentially expressed genes (DEGs) in patients with dermatomyositis-associated interstitial lung disease (DM-ILD) and healthy controls. A total of 2,018 DEGs were identified between DM-ILD and healthy blood samples. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis showed that DEGs were mainly involved in immune- and inflammatory-related biological processes and pathways. Disease ontology (DO) enrichment analysis identified 35 candidate key genes involved in both skin and lung diseases. Meanwhile, a total of 886 differentially expressed alternative splicing (AS) events were found between DM-ILD and healthy blood samples. After overlapping DEGs with differential AS genes, the plasminogen activator and urokinase receptor (PLAUR) involved in immune-related biological processes and complement and coagulation cascades was screened and identified as the most important gene associated with DM-ILD. The protein–protein interaction (PPI) network revealed that PLAUR had interactions with multiple candidate key genes. Moreover, we observed that there were significantly more neutrophils and less naive B cells in DM-ILD samples than in healthy samples. And the expression of PLAUR was significantly positively correlated with the abundance of neutrophils. Significant higher abundance of PLAUR in DM-ILD patients than healthy controls was validated by RT-qPCR. In conclusion, we identified PLAUR as an important player in regulating DM-ILD by neutrophil-associated immune response. These findings enrich our understanding, which may benefit DM-ILD patients.